Effects of preoperative dexmedetomidine on the occurrence of postoperative delirium in adult cardiac surgery patients - Mishra, Sharad Chandrika; Chowdhury, Sudip (International Journal of Research in Medical Sciences, 2023)
Background: Postoperative delirium (POD) is a serious complication in elderly patients undergoing cardiac surgery. This study was aimed at investigating the effect of perioperative administration of dexmedetomidine for general anesthesia maintenance on occurrence and duration of POD in elderly patients after cardiac surgery. Methods: This randomized control trial was done in central India after the institution’s ethical committee gave their approval. One hundred and sixty-four patients were enrolled after cardiac surgery. Each patient gave their written consent after being fully informed. Patients over 60 years’ old who were going to have heart surgery were included in the study. Results: The difference in POD incidence between the dexmedetomidine and propofol groups was not statistically significant (p=0.0758). When compared to patients receiving propofol, patients receiving dexmedetomidine had a median delirium onset time that was delayed (second day vs. first day) and a shorter median delirium duration (2 days versus 3 days). Additionally, the patients receiving dexmedetomidine showed a lower VAS score and less use of opiate analgesics. Regarding other postoperative results, no difference was seen. Conclusions: Dexmedetomidine administration during cardiac surgery decreased the incidence, postponed the onset, and shorten the duration of POD in elderly patients.